Identification of an LPS-Induced Chemo-Attractive Peptide from Ciona robusta - Valeria Longo; Alessandra Longo; Annamaria Martorana; Antonino Lauria; Giuseppa Augello; Antonina Azzolina; Melchiorre Cervello; Paolo Colombo (Marine Drugs, 2020)
Background: Previously published work has demonstrated that the LPS injection of Ciona robusta leads to the overexpression of a truncated form of an immune-related mRNA (C8short) by means of Ciona robusta (CR) alternative polyadenylation (APA) (CR-APA). Methods: The 3D structure of the C8short-derived Ciona robusta chemo-attractive peptide (CrCP) was evaluated by homology modeling. The biological activity of the CrCP was studied in vitro using a primary human dermal cell line (HuDe). Real-Time PCR was used to investigate the expression levels of genes involved in cell motility. NF-κB signaling was studied by western blotting. Results: In silico modeling showed that CrCP displayed structural characteristics already reported for a short domain of the vertebrate CRK gene, suggesting its possible involvement in cell migration mechanisms. In vitro assays demonstrated that CrCP was capable of inducing the motility of HuDe cells in both wound healing and chemo-attractive experiments. qPCR demonstrated the capability of CrCP to modulate the expression of the matrix metalloproteinase-7 (MMP-7) and E-cadherin genes. Finally, western blot analysis demonstrated that treatment with CrCP induced activation of the NF-κB signaling pathway. Conclusion: Our results describe the characterization of the 3D structure and chemo-attractive activity of an LPS-induced CrCP peptide from Ciona robusta.